Pengungkapan Corporate Social Responsibility dan Kinerja Keuangan Perusahaan Perbankan - Widyasari, Ni Made; Yadnyana, Ketut (E-Jurnal Akuntansi; Vol 31 No 7 (2021), 2021)
A company Development can made the ekspoitation of natural resources to be higher, so it is important for the companies to carry out CSR activities. This study aims to determine the effect of corporate social responsibility disclosure on financial performance in Bank sector as proxied by eeturn on assets (ROA) and return on equity (ROE). The sample was obtained using purposive sampling method and the number of research samples was 19 companies with a total of 95 observations. The data analysis technique in this study was panel data regression analysis. The results show that corporate social responsibility (CSR) disclosure has a positive and significant effect on financial performance in bank sector as proxied by return on assets (ROA) and return on equity (ROE). The implication of this research can contribute to the empirical study of stakeholder theory and equity theory. The implication of this research is that it can be taken into consideration in decision making by stakeholders and company management. Keywords: CSR Disclosure; ROA; ROE.